What is the role of the library in a modern university? A Bourdieusian analysis. - Williams, Caroline Ann (2025)
This thesis examines various perspectives on the role of the university library in contemporary Western universities, tracing its evolution and strategic development. Technological advancements and neoliberal shifts in higher education have driven significant changes; transforming spaces, collections, services, and staff. Despite positive developments, current challenges include budget constraints and a perceived decline in the library’s importance.